KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN KINERJA GURU DI LEMBAGA PENDIDIKAN ISLAM - lutfi firdausi; Achmad Patoni; Binti Maunah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Effective and efficient leadership will be realized if carried out based on the functions and objectives that have been set. A leader should strive to be part of the situation of the group or organization he leads. This type of research includes library research. Data collection techniques in this study are documentation, which is looking for data about things or variables in the form of notes, books, papers or articles, journals and others. The research instruments in this study are a check-list of classification of research materials, writing schemes / maps and research record formats. In this study using data analysis techniques in the form of content analysis. Content analysis is a scientific analysis of the message content of a data. The result of this study is that leadership determined by a manager in an organization can create harmonious integration and encourage passion in doing work to achieve maximum goals. In leadership there are many styles in it, of course, each style has its own advantages and disadvantages